Effect of Nitrogen Levels and Growth Retardants on Cotton Under High Density Planting System - , K. B. Sankat; , M. M. Patel; , P. S. Patel; , H. R. Ramani (Archives of Current Research International, 2025)
Trials were conducted during three years from 2021-22 to 2023-24 at Main Cotton Research Station, Navsari Agricultural University, Surat, Gujarat to study the effect of nitrogen levels on yield of cotton and to find out the efficacy of growth retardants on plant canopy of cotton grown under high density planting system. Nine treatment combinations comprising of three nitrogen levels viz; 375 kg N/ha, 300 kg N/ha and 225 kg N/ha with three treatments of growth retardants viz; Cycocel spray @ 50 g a.i./ha in each spray at 60 and 75 days after sowing, Mepiquat chloride spray @ 37.5 g a.i./ha in each spray at 60 and 75 days after sowing and Control (water spray at 60 and 75 days after sowing) were laid out in factorial randomized block design. Nitrogen levels significantly influenced on growth parameters viz; plant height, number of sympodial branches/plant, sympodial length and days to 50 % flowering, yield attributes viz; number of bolls/plant and boll weight, seed cotton yield (kg/ha), lint yield (kg/ha) and stalk yield (kg/ha). Important growth and yield parameters viz; plant height, number of sympodial branches/plant, sympodial length, days to 50 % flowering, number of bolls/plant and boll weight, seed cotton yield (kg/ha), lint yield (kg/ha) and stalk yield (kg/ha) were significantly influenced by growth retardant treatments. Conclusion of the experiment was drawn that application of 300 kg nitrogen/ha in five equal splits at 30, 60, 75, 90 and 105 days after sowing along with 40 kg P2O5/ha as basal dose and spraying of mepiquat chloride 5 % AS @ 37.5 g a.i./ha at 60 and 75 days after sowing found optimum for obtaining higher seed cotton yield as well as net returns from Bt cotton hybrid grown with high density planting system maintaining 60 x 45 cm spacing under irrigated condition of south Gujarat.